The five-factor model of personality across cultures - McCrae, Robert R. (Boston, MA : Springer US : Imprint: Springer, 2002., 2017)
The Five-Factor Model Across Cultures was designed to further an understanding of the interrelations between personality and culture by examining the dominant paradigm for personality assessment - the Five-Factor Model or FFM - in a wide variety of cultural contexts. Data from 40 cultural groups, ranging from Vietnamese Americans to Zimbabweans, are used to address a variety of issues: Is the FFM universal? Do personality traits have the same correlates in different cultures? How are mean levels of personality traits related to features of cultures, such as Individualism/Collectivism? Are stereotypes of national character accurate? The book is unified by the use of a single model of personality, and, in most cases, a single instrument, the Revised NEO Personality Inventory. Many of the chapters provide psychometric evaluations of new translations of this instrument. However, all chapters view personality assessment in cultural context. Diverse points of view are represented on how personality is related to culture, and a methodological chapter provides a critical assessment of the body of work. The editors provide an overview and a concluding chapter that evaluates findings in the book from the perspective of the bio-social Five-Factor Theory of personality.